DISTRIBUSI KEJADIAN DIFTERI MENURUT CAKUPAN IMUNISASI DPT-HB-HIB DAN KEPADATAN PENDUDUK DI KOTA SURABAYA - Shindy Ayu Anggraini; Lucia Yovita Hendrati (Media Gizi Kesmas, 2023)
Background: Diphtheria is a "re-emerging disease" because diphtheria cases had fallen in 1985 and increased again in 2005 when an outbreak occurred in East Java. Immunization coverage in the city of Surabaya has reached the target of > 95%, the incidence of measles still exists and has doubled in 2018. Objectives: Analyzing the distribution map of diphtheria incidence according to DPT-HB-Hib immunization coverage and population density in the city of Surabaya. Methods: This study uses a descriptive analytic type with a correlation study design. The population is 31 districts in the city of Surabaya. Data was taken from the Health Profile of the City of Surabaya in 2017, 2018 and 2019. Data processing used the Health Mapper application version 4.3.2 to analyze data descriptively. Results: The distribution of diphtheria incidence with immunization coverage and population density in the city of Surabaya in 2017, 2018 and 2019 shows that the incidence of diphtheria is fluctuating in 2019 with immunization coverage and population density increasing each year. Conclusions: The incidence of diphtheria in the city of Surabaya shows that every time there is a decrease in immunization coverage it tends to cause new cases and an increase in diphtheria cases in the area. Population density is one of the factors for the rapid transmission of diphtheria bacteria.